Pancreatic Lipase Inhibitory Activity of Endophytic Actinobacteria from Rhododendron spp. - Witri Winanda; Irmanida Batubara; Yulin Lestari (Biosaintifika: Journal of Biology & Biology Education, 2021)
Antiobesity medication is available as therapeutic compounds that can reduce fat digestion by the inhibition of pancreatic lipase. Actinobacteria have the potency as source of bioactive compounds with various biological function including as pancreatic lipase inhibitor.  However, the potency of endophytic actinobacteria from Rhododendron spp. as source of pancreatic lipase inhibitor producer has not been reported yet. The aim of this study was to examine the potential of pancreatic lipase inhibitory activity of 23 endophytic actinobacteria from Rhododendron spp.; to characterize their colony based on morphology and molecular analysis. Screening test of pancreatic lipase inhibitor was conducted using the supernatant of endophytic actinobacteria, lipase pancreatic porcine (L3126) and p-nitrophenyl butyrate. The supernatant of selected isolates was extracted using ethyl acetate. The result showed that various inhibitory activities ranging between 0.00 until 91.69%. There were 11 out of 23 isolates that have potential as pancreatic inhibitor. Amongst them, the extract of four selected isolates, i.e. RZP 1.3, RSSB 3.2, RSS 2.1, and RJB F3.2 demonstrated inhibitory percentage of more than 80%. The RJB F3.2 extract showed to have IC50 value by 431.48 µg mL-1 compared to control, i.e. Xenical (89.07 µg mL-1). Phytochemical analysis exhibited that the extract of the selected isolates contained alkaloid which may function as pancreatic lipase inhibitor. Based on the morphological character, the selected isolates have various morphological colonies and 16S rRNA gene sequence revealed the sequence homology to Streptomyces spp. The data clearly indicate that endophytic actinobacteria from Rhododendron spp. have potency as pancreatic lipase inhibitor producer and further studies could be explored for the development of antiobesity agent.